پیر مہر علی شاہؒ کی منتخب نعتیہ شاعری میں سیرتِ طیبہ ﷺ کا جمالیاتی اظہار - Hassan Mujtaba (Seerat Studies, 2025)
This study explores the aesthetic representation of the Seerat-un-Nabiﷺ in the Na‘at poetry of Pir Meher Ali Shah Golravi (1859–1937), focusing on his poetic collection Mirat-ul-Irfan. A prominent Sufi poet of the Indian subcontinent, Pir Meher Ali Shah combines spiritual depth, literary elegance, and intense love for the Prophet Muhammad ﷺ in his verses. His Na‘at poetry transcends mere praise and becomes a profound spiritual and artistic portrayal of the Prophet's ﷺ character, appearance, and significant events from his life such as the Mi‘raj and Hijrah. Using refined metaphors, rhythmic cadence, and emotionally resonant imagery, the poet presents themes of prophetic beauty, moral excellence, intercession, and divine unity. The famous Na‘at “Aj sakh mitraan di vadhairi ae” epitomizes this harmonious blend of devotional intensity and aesthetic expression. The research concludes that Pir Meher Ali Shah’s poetry is not only a tribute to the Prophet ﷺ but a mystical invitation that fosters an inner connection with the Seerah through love, reverence, and poetic beauty.